Supremacy of English Language Proficiency: Identity Transmission and Transgression among Bangladeshi Graduates - Islam, Md Tarikul; Ramalingam, Selvajothi; Hoque , Kazi Enamul (Issues in Language Studies, 2022)
The study focuses on the language use of Bangladeshi graduates and how they deal with the local Bengali language with English as an international language. The study investigates whether the perception of ELP promotes identity transmission or transgression. The study is conducted with a mixed-method approach using a triangulation research design with a convergence model. Questionnaire data were collected from 370 respondents consisting of three groups of graduates according to educational qualifications, income level, and living places. The findings indicate that ELP may be disadvantageous to the local culture and results in the use of mixed languages. The results suggest that ELP accelerates a form of language and cultural transgression that reshapes personality and erodes the traditional local culture and heritage language identity among Bangladeshi graduates.